Hubungan Antara Pembelajaran Mendalam Dan Pengembangan Karakter Literat Siswa Sekolah Dasar Dalam Mata Pelajaran Bahasa Indonesia - Rahmad Taufik (Prodi PGSD Unsultra, 2025)
The 21st-century education paradigm emphasizes a shift from teacher-centered to student-centered learning that fosters critical thinking, reflection, and character development. This study aims to analyze the relationship between deep learning and the development of literate character in Indonesian language learning at the elementary school level. The research employed a qualitative descriptive literature review method by analyzing ten accredited national journal articles focused on Indonesian language instruction, literacy, and student character formation. The findings reveal that deep learning significantly contributes to developing literate character through reflective, collaborative, and contextual learning activities. Strategies such as project-based learning and contextual teaching and learning effectively enhance students’ critical thinking, empathy, and social responsibility. Furthermore, the integration of the Merdeka Curriculum and the Pancasila Student Profile strengthens the synergy between cognitive and affective aspects of learning. The main challenges in implementation include teachers’ limited competencies, instructional time constraints, and inadequate literacy resources in schools. Therefore, continuous professional development and institutional support are essential to foster a strong literacy culture in primary education. Conceptually, deep learning serves as a foundation for developing literate character that is adaptive, reflective, and grounded in humanistic values.